Exosomal miRNA-155 and miRNA-146a are promising prognostic biomarkers of the severity of hemorrhagic fever with renal syndrome - Irina Gilyazova; Elizaveta Ivanova; Valentin Pavlov; Guzel Khasanova; Aliya Khasanova; Adel Izmailov; Dilara Asadullina; Gulshat Gilyazova; Guoqing Wang; Ilgiz Gareev; Ozal Beylerli; Elza Khusnutdinova (Non-coding RNA Research, 2023)
Introduction: Hemorrhagic fever with renal syndrome (HFRS), caused by Orthohantaviruses, occupies one of the leading places among natural focal human diseases, for which there are no modern accurate and highly sensitive diagnostic methods. To improve this situation, a better understanding of the Hantavirus pathogenesis of HFRS is required. Determination of the expression level of exosomal microRNAs (miRNAs) in the serum/plasma of patients makes them potential biomarkers for diagnosing and predicting HFRS. The purpose of this study was to analyze the expression level of miRNA-146a, miRNA-126, miRNA-218, miRNA-410, miRNA-503 and miRNA-155 in patients with HFRS at different stages (fever stage, polyuric stage and convalescence stage) and with different severity of the course this disease Materials and methods: The moderate group of patients with HFRS included 105 patients, the severe group included 99 patients, and the severe group with complications included 84 patients. Blood samples from patients with HFRS for molecular genetic analysis were collected three times: during the initial febrile period (days 1–4 of illness), the polyuric period (days 15–22 of the disease), and during convalescence. Total RNA isolation was performed using the exoRNeasy Midi Kit (Qiagen, Germany). Quantitative real-time PCR (qRT-PCR) was performed using the miRCURY LNA SYBR Green PCR Kit (Qiagen, Germany) and the LightCycler96 real-time PCR product detection system (Roche, Switzerland). Results: When comparing the expression level of exosomal miRNAs in groups of patients with different severity of the disease, a statistically significant increase in the expression level of miRNA-146a was revealed in patients with severe HFRS with complications (Fold change 2.694; p = 0.0022) compared to the group with a moderate disease form, as well as an increase in miRNA-155 expression in patients with severe and severe HFRS with complications compared to the moderate form (Fold change 1.861; p = 0.0492; Fold change 1.976; p = 0.001, respectively). Comparative analysis of the expression level of other miRNAs in patients with HFRS at various stages and with different severity of HFRS did not reveal any statistically significant results (P > 0.05). Conclusions: MiRNA-155 and miRNA-146a may be promising prognostic biomarkers in HFRS. However, further investigations are needed to evaluate the changes in the expression of miRNAs and the network of genes that can be potential targets for the studied miRNAs in order to elucidate the molecular mechanisms that can influence the occurrence and development of HFRS.